Storm surge simulation for Myanmar using IIT-D model - Maw, Khin Win; Argete, Amador C. (Quezon City Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliiman, 2009)
A numerical storm surge prediction model developed in IIT-D (Indian Institute of Technology, Delhi) was used to simulate surge heights by applying actual parameters for storms which made landfall in Myanmar. The numerical model was tested on the sensitivity of the predicted surge heights with varying water depth and storm parameters such as pressure drops, maximum sustained wind speed, the radius of maximum wind, duration of the storm and landfall angles. Results indicate that the shallowness of the water in coastal areas may considerably magnify the surge heights in the region. Obtuse landfall angle generated the highest surge in Rakhine coast and perpendicular landfall angle had the highest surge in the Delta coast. Higher surge are associated with larger pressure drop, maximum sustained wind and radius of maximum wind. The experiments show that a slow moving cyclone results in maximum surge compared to a fast moving cyclone.
Thesis (Master of Science in Meteorology)--University of the Philippines Diliman
Keywords: Storm surges -- Myanmar